Agricultural credit through co-operatives and other institutions - Food and Agriculture Organization of the United Nations; Food and Agricultural Organization of the United Nations (Rome : Food and Agricultural Organization of the United Nations, 1965)
This volume examines how cooperatives and other institutions provide agricultural credit with specific reference to: utilisation of credit; character of agricultural production and credit needs; nature of agricultural production and credit; agricultural credit and extension education; agricultural credit institutions in general; cooperative credit and state policy; the role of central banks and agricultural finance.
Includes bibliographical references. : p. (211)-212.
lje 24/01/2019
Loans
Keywords: Agricultural credit; Agricultural cooperative credit associations; Agricultural finance; Agricultural extension; Co-opertive credit; Developing countries